2016
DOI: 10.1007/s00572-016-0699-y
|View full text |Cite
|
Sign up to set email alerts
|

New mutualistic fungal endophytes isolated from poplar roots display high metal tolerance

Abstract: This study aimed to isolate, identify, and characterise metal-tolerant fungi colonising poplar roots at a metalcontaminated phytoremediation site. Poplar roots were colonised by arbuscular mycorrhizal, ectomycorrhizal, and endophytic fungi, and the species were determined by ITS molecular analyses. Eight different isolates were successfully isolated into pure culture. Three isolates belonging to the Helotiales (P02, P06) and the Serendipita vermifera species (P04) were highly tolerant to metals (Cd, Zn, Pb, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Values observed in this soil were four to six times higher than in local reference agricultural soils as reported by Lamy et al (2006). The overall characteristics of the site have been provided previously (Lacercat et al, 2016;Foulon et al, 2016). The physico-chemical characterization of the soil (Table 1) was performed by the SADEF laboratory (Aspach-le-bas, France) (COFRAC certificate N° 1-0751).…”
Section: Soil Physico-chemical Propertiesmentioning
confidence: 85%
“…Values observed in this soil were four to six times higher than in local reference agricultural soils as reported by Lamy et al (2006). The overall characteristics of the site have been provided previously (Lacercat et al, 2016;Foulon et al, 2016). The physico-chemical characterization of the soil (Table 1) was performed by the SADEF laboratory (Aspach-le-bas, France) (COFRAC certificate N° 1-0751).…”
Section: Soil Physico-chemical Propertiesmentioning
confidence: 85%
“…Likar & Regvar [243] found that DSEs reduced the metal uptake by the Salix caprea L. cuttings, thus suggesting a beneficial role for S. caprea in metal-enriched soils. Similarly, four fungal root endophytes were found to be highly tolerant to metals (Cd, Zn, Pb, and Cu), further highlighting the potential use of these endophytic strains for tree-based phytoremediation of metal-contaminated sites [244]. It is possible that under stressful environments, the interactions between plants and root fungal endophytes could switch from neutral to beneficial, and in that sense, could be counted as constituting a mutualistic relationship [245].…”
Section: Root Endophytes and Tree Healthmentioning
confidence: 96%
“…A total of 21 isolates belonging to the DSE-2 group and two isolates belonging to the DSE-5 group sensu Knapp et al (2012) originating from different hosts and geographic regions (TABLE 1) were examined in the present study. The sampling sites were previously described in Kovács and Szigetvári (2002), Knapp et al (2012), Glynou et al (2015), Lacercat-Didier et al (2016 and Ashrafi et al (2017).…”
Section: Origin Of Isolatesmentioning
confidence: 99%
“…All those isolates were able to colonize roots of hybrid Populus in re-synthesis experiments. The clade including these and other sequences was described as a "new endophytic putative species belonging to the Helotiales" (Lacercat-Didier et al 2016).…”
Section: Introductionmentioning
confidence: 99%